Single-leg countermovement jump compensation assessment: Content validity of a checklist - Dudagoitia Barrio, E.; Hernández-García, R.; Ramirez-Campillo, R.; Garcia-Atutxa, I.; Villanueva-Flores, F.; García-de-Alcaraz, A. (International Journal of Sports Medicine, 2024)
Jump actions are common in several sports, and their performance is related to a myriad of biomechanical and physiological factors, with links to athletic performance and imbalances. Currently, a valid, field-based, easy-to-use tool to assess the quality of an explosive jump movement, similar to the required sports movements, is unavailable. Thus, the present study aimed to design and validate a field-based, easy-to-use tool that can be used to assess the quality of movement during an explosive single-leg countermovement jump (SL-CMJ). Ten experts participated in the content validation process for the checklist, including checking item relevance, definition accuracy, and scoring adequacy. Content validity was measured using the Aikens V format. The checklist included the items "Foot orientation," "Knee valgus/varus," "Internal/external hip flexed orientation," "Pelvis tilt," "Thorax tilt," "Thorax rotation," "Foot pronation/supination," "Asymmetrical hip," and "Lumbo-pelvic association". The items achieved a 0.60-0.99 in relevance, 0.70-1.00 in definition accuracy, and 0.80-0.83 in scoring adequacies in the Aikens V proof. The results from the context validation process suggest that the tool may be appropriate to assess athletes' quality of explosive movement. Furthermore, the results derived from such assessments may help to design better and safer training interventions.